2018
DOI: 10.1111/fwb.13204
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐water availability governs survival of an amphibian in arid mountain streams

Abstract: Declines in amphibian populations worldwide have been linked to multiple factors, including recent changes in climate. Changes in precipitation, for example, can alter the availability of aquatic resources that are required by many amphibians for successful reproduction and larval development. Changes in climate have the potential to affect other important demographic parameters, particularly for species that are active year‐round. Therefore, we studied survival of post‐metamorphic (snout‐vent length ≥50 mm) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…We opted for the simpler approach given that lowland leopard frogs have limited dispersal capabilities and low rates of post‐metamorphic survival (Zylstra et al. ). Finally, we allowed detection probability to vary between spring and fall sampling periods, vary with observer experience, and vary with availability of surface water: logitpi,k,t=normalαp+normalβp.fallfallt+normalβp.obsobsi,k,t+normalβp.waterwateri,k,t+normalβp.water2wateri,k,t2where α p is mean detection probability of experienced observers in spring on the logit scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We opted for the simpler approach given that lowland leopard frogs have limited dispersal capabilities and low rates of post‐metamorphic survival (Zylstra et al. ). Finally, we allowed detection probability to vary between spring and fall sampling periods, vary with observer experience, and vary with availability of surface water: logitpi,k,t=normalαp+normalβp.fallfallt+normalβp.obsobsi,k,t+normalβp.waterwateri,k,t+normalβp.water2wateri,k,t2where α p is mean detection probability of experienced observers in spring on the logit scale.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, we might have modeled d B;i;j;t instead of d B;i;t and incorporated covariates to represent differences in habitat characteristics between sites i and j, similar to other gradient-based approaches that have been used for birds (Broms et al 2016). We opted for the simpler approach given that lowland leopard frogs have limited dispersal capabilities and low rates of post-metamorphic survival (Zylstra et al 2019). Finally, we allowed detection probability to vary between spring and fall sampling periods, vary with observer experience, and vary with availability of surface water:…”
Section: Model Implementation and Inferencesmentioning
confidence: 99%
“…Droughts can also trigger wildfires (Littell et al, 2016), which in turn can have deleterious effects on amphibians (Zylstra et al, 2019), fishes (Turner et al, 2015) and invertebrates (Robson et al, 2018; Verkaik et al, 2015) populations and communities. For example, Zylstra et al (2019) showed that leopard frog populations declined during drought years and downstream of sites exposed to wildfires due to increased post‐fire erosion. Robson et al (2018) also found that fires and droughts could have antagonistic effects on the invertebrate communities of Australian streams.…”
Section: Ecohydrological Interactions In Ires During Droughtsmentioning
confidence: 99%
“…Such warming may induce increased and premature organism mortality, as well as changes in microbial (Arias Font et al, 2021) and fish activity (Mameri et al, 2020). Droughts can also trigger wildfires (Littell et al, 2016), which in turn can have deleterious effects on amphibians (Zylstra et al, 2019), fishes (Turner et al, 2015) and invertebrates (Robson et al, 2018; Verkaik et al, 2015) populations and communities. For example, Zylstra et al (2019) showed that leopard frog populations declined during drought years and downstream of sites exposed to wildfires due to increased post‐fire erosion.…”
Section: Ecohydrological Interactions In Ires During Droughtsmentioning
confidence: 99%
“…Instead, as employed in the present study, the measurement of isotope composition (δ 2 H, δ 18 O) of related water components offers the opportunity for understanding the budgets of water in natural soil–plant systems. Most studies on the isotopic composition of dew have been carried out in arid and semiarid regions. Humid grassland has rarely been studied, although even there small amounts of water from dew formation can be highly beneficial for plants . Dew may become even more important in humid grassland in cases where leaves were detached from their roots and the soil water source to produce silage or hay.…”
Section: Introductionmentioning
confidence: 99%